Spatial models of rice fields change and sustainable agriculture in Solok District, West Sumatra Province - Umar, Iswandi; Arif, Dian Adhetya (Brawijaya University, 2023)
Indonesia is an agricultural country and one of the world's rice-producing countries. However, the increase in population has pushed for the conversion of agricultural land to non-agricultural purposes. Solok is a district with the largest paddy field area in West Sumatra. Yet, the increase in population has resulted in a decrease in paddy fields every year. This study aimed to determine the model for changing the area of paddy fields for the 2000-2020 period and determine the direction of sustainable agricultural policies. In defining the paddy field change model, this research uses the input data from the interpretation of 2000 Landsat 5 imagery, 2010 Landsat 7 imagery, and 2020 Landsat Oli 8 imagery. The data were analyzed using a geographic information system (GIS). This research employed the Powersim Software with a system dynamics approach in projecting rice production and demand. This research used Interpretative Structural Modeling (ISM) analysis to determine the direction of sustainable food policy. The results showed that there had been a conversion of 13,801.6 hectares of paddy agricultural land into a built-up area in the 2000-2020 period in Solok District. In 2020, Solok District supplied 2,838 thousand tons of rice, while the demand for rice was 446.3 thousand tons. In the direction of the sustainable agriculture policy, there are three key sub-elements; tightening land use permits, establishing and implementing spatial planning regulations, and consistency in enforcing spatial planning violation laws.